2021
DOI: 10.3389/fphys.2021.773878
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Reparative Dentin Formation Using Apigenin Local Delivery in the Exposed Pulp Cavity

Abstract: Apigenin, a natural product belonging to the flavone class, affects various cell physiologies, such as cell signaling, inflammation, proliferation, migration, and protease production. In this study, apigenin was applied to mouse molar pulp after mechanically pulpal exposure to examine the detailed function of apigenin in regulating pulpal inflammation and tertiary dentin formation. In vitro cell cultivation using human dental pulp stem cells (hDPSCs) and in vivo mice model experiments were employed to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…To date, various animal DCP models have been developed to evaluate reparative dentin formation 29,30) . These DCP models are roughly classified as pulp-exposed models 31,32) and non-pulp-exposed models 33,34) . Pulp exposure increases the risk of inducing pulp necrosis 35,36) , which potentially veils the cellular behavior of senescent cells for reparative dentin formation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, various animal DCP models have been developed to evaluate reparative dentin formation 29,30) . These DCP models are roughly classified as pulp-exposed models 31,32) and non-pulp-exposed models 33,34) . Pulp exposure increases the risk of inducing pulp necrosis 35,36) , which potentially veils the cellular behavior of senescent cells for reparative dentin formation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on ER regulation and vesicle trafficking made use of chemical chaperone treatments to subdue a range of incurable diseases ( Singh et al, 2008 ; Luo et al, 2010 ; Wu et al, 2020 ). Similarly, in this study, in order to modulate the excessive inflammatory environment and promote dentin regeneration after pulp exposure, we examined the function of the chemical chaperone 4PBA, one of the candidate drugs for relieving ER stress, an important cellular step for protein formation and secretion in regeneration, and as a drug repositioning approach, in exposed pulp cavity for 3, 5, and 42 days, using a well-established animal model system ( Jung et al, 2017 ; Aryal et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mice were sacrificed after 3, 5, and 42 days from drug treatment for immunological and histological analyses as described previously ( Jung et al, 2017 ; Aryal et al, 2021 ). Primary antibodies were directed against NESTIN (1:400; cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apigenin, a natural flavonoid with strong antioxidant, and anti-inflammatory properties, could upregulate several osteogenesis-related signaling molecules, such as osteocalcin (OCN), bone sialoprotein (BSP), runt-related transcription factor 2 (RUNX2), BMP2, BMP4, and BMP7 in hDPSCs post 14 days of treatment [ 235 ]. This study also confirmed the role of apigenin in facilitating dentin-bridge formation with few irregular tubules in mice pulpal cavities after 42 days of treatment with apigenin [ 235 ]. Tanshinone IIA is a diterpene quinone derived from Salvia miltiorrhiza, and has been reported to induce hPDLSC osteogenesis via the ERK1/2-Runx2 axis signaling pathway [ 236 ].…”
Section: Botanicals In Oral Stem Cell-mediated Regenerationmentioning
confidence: 99%